SIMULATION STUDY OF THE PHOTOTRANSPORT IN AMORPHOUS SEMICONDUCTORS FROM TIME-OF-FLIGHT PHOTOCURRENT ANALYSIS - Serdouk, Fadila; Benkhedir, Mohamed-Lotfi (University of Eloued جامعة الوادي, 2018)
Time -of -flight transient photocurrent has been numerically analyzed. It is shown that the charge –carrier transit time can be determined in both non-dispersive and dispersive transport. It is also shown that the localized state distributions can be determined from the analysis of the photocurrent
Séminaire National Sur Laser Solaire Et Matériaux ElOeued 5-6 Février 2018
Keywords: Amorphous semiconductor, Density of localized states, Phototransport, Time-offlight, Inverse Laplace transform